Bibliometric analysis of pharmacist's research on antimicrobial stewardship in Japan: an interrupted time series analysis on the implementation of the certification system for infection control pharmacists - Masayuki Maeda; Takefumi Miyake; Ryo Inose; Satoru Ueda; Ken-ichi Matsugi; Yuichi Muraki; Takashi Kitahara (BMC, 2021)
Abstract Background Pharmacist plays an integral role in promoting antimicrobial stewardship (AS) strategies by committing to the evidence-based activities in this field. The present study aims to document trends in actual achievements through bibliometric analysis and identify the future direction of pharmacists with expertise in AS by describing the characteristics of articles on AS written by Japanese pharmacists. Methods The study searched for articles written in Japanese and English on Ichushi-Web and MEDLINE, respectively, until December 2020 for published articles relevant to AS. The articles were classified into the seven groups according to content. Interrupted time series analysis (ITSA) was performed to identify the effect of the certification system for infection control pharmacy specialists (ICPSs) on the number of articles in Japanese. Results The study retrieved 476 and 145 titles from Ichushi-Web and MEDLINE, respectively, out of which 383 and 123 articles written in Japanese and English, respectively, were considered relevant to AS. A continued publication was found for Japanese articles written by pharmacists assigned to large-sized hospitals since 1998, whereas few articles in English were published until 2017. The most frequent content of articles in both languages was intervention (56.7 and 59.0%, respectively). ITSA indicated that the number of publication slightly increased before [β1 = 1.33, 95% confidence interval (CI): − 0.62-3.28; P = 0.169] the implementation of the system. Moreover, the level (β2 = 11.41, 95%CI: − 0.23-23.05; P = 0.054) increased after the implementation of the system, whereas the slope decreased (β3 = − 2.07, 95%CI: − 4.16-0.03; P = 0.053). However, the changes were not statistically significant. Conclusion The study identified the contribution of pharmacists by documenting trends in AS practice and by conducting bibliometric analysis. The implementation of the ICPS certification system positively influenced the trend of publications. Therefore, the study recommends that policymakers and stakeholders should promote and support the evidence-based activities for AS for pharmacists in small- to medium-sized hospitals.